PENGARUH SERVANT LEADERSHIP, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN HAMAKA BALI ADVENTURE - Putu Ira Tresna Yanti; Ni Putu Yeni Astiti; I Nyoman Resa Adhika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
The success and failure of a company is often determined by the important role of its human resources. There are many factors that influence employee performance, including servant leadership, motivation and work discipline. Likewise at Hamaka Bali Adventure, servant leadership, motivation and work discipline are factors that can influence employee performance. There is attention and findings regarding the issues of servant leadership, motivation and work discipline in an effort to improve and increase employee performance in accordance with the aim of this research to determine the influence of servant leadership, motivation and work discipline on employee performance at Hamaka Bali Adventure. The population in this study was 35 person. The number of samples in this study was 35 people. The sampling technique used is a saturated sampling technique. Data analysis in this study used Multiple Linear Regression Analysis using the IBM SPSS Statistics 25 application. The results of the study showed that 1). Servant leadership has a positive and significant effect on employee performance at Hamaka Bali Adventure. 2). Motivation has a positive and significant effect on employee performance at Hamaka Bali Adventure. 3). Work discipline has a positive and significant effect on employee performance at Hamaka Bali Adventure.